Non-canonical Roles of Complement in the CNS: From Synaptic Organizer to Presynaptic Modulator of Glutamate Transmission - Pittaluga, Anna; Torre, Veronica; Olivero, Guendalina; Rosenwasser, Nicole; Taddeucci, Alice (Current Neuropharmacology, 2025)
The central nervous system (CNS) is not an immune-privileged compartment, but it is intimately intertwined with the immune system. Among the components shared by the two compartments is the complement, a main constituent of innate immunity, which is also produced centrally and controls the development and organization of synaptic connections. Complement is considered a doubled-faced system that, besides controlling the physiological development of the central network, also subserves synaptic engulfment pivotal to the progression of neurodegenerative diseases. Quite interestingly, besides these “canonical” roles, evidence in the last two decades highlighted other “non-canonical” role(s), thereby complementing modulates chemical transmission at central synapsis. It emerged that glutamate is the preferential target of these “non-canonical” complement-induced effects, which include i) the control of the release of glutamate from neurons and astrocytes and ii) the control of the number and the functions of central glutamatergic receptor subtypes (i.e., the NMDA receptors, the AMPA/kainate receptors, and the metabotropic glutamate receptors) in plasma membranes. This review summarizes some of the available results supporting the role of complement as a “modulator” of central glutamate transmission, paying particular attention to those events that occur presynaptically. Taking into consideration the enormous progress in complement pharmacology and the increasing number of therapeutics in clinical trials, deepening our knowledge of these” non-canonical” role(s) could pave the road to new therapeutic approaches for the management of central neurological diseases.
Keywords: glutamate